TRANSCENDING THE DUALISMS OF ACTIVITY THEORY. - NUNEZ, ISKRA (Journal of Critical Realism, 2013)
This article employs the basic tenets of critical realism to provide a philosophical foundation for understanding and resolving the dualisms of activity theory. Its argument follows in four parts. (1) First I develop an immanent critique that shows the problems within activity theory; it reveals that several dualisms were present from the onset, and further that an implicit ontology allows activity theorists to presuppose (aspects of) critical realism in practice. I claim that the historical development of activity theory is marked by attempts to resolve contradictions, which are signalling devices pointing to the need for theoretical expansion. (2) To shed light on attempts to mend dualisms, I then introduce the notion of a 'patch' because it functions as a mechanism that sustains dualisms and gaps in practice. (3) An omissive critique identifies the key omitted element (or absence) that causes the dualisms; namely, the omission of a critique of Humean philosophy and classical empiricism. Finally, (4), after effectively isolating and explaining the source of dualisms, I prepare the ground for a proto-explanatory critique to rectify them.